Nagoya Protocol and Infectious Diseases: Hindrance or Opportunity? - Lajaunie, Claire; Morand, Serge (Frontiers in Public Health, 2020)
While strong concerns have emerged in the health science community over the application of the Nagoya Protocol concerning the sharing of pathogens (and microbiota) collected from humans, specific issues are not solved in relation to the implementation of the Nagoya Protocol. These issues should be put under scrutiny by legal researchers together with scientists from different disciplines (such as human medicine, health anthropology, global health).